2016
DOI: 10.1186/s12967-016-0997-3
|View full text |Cite
|
Sign up to set email alerts
|

Could patents interfere with the development of a cardiovascular polypill?

Abstract: BackgroundThe Wellcome Trust, the World Health Organization, and cardiologists have advocated for the idea of a “polypill” containing multiple cardiovascular drugs to be co-formulated into a single pill for over a decade. Some cardiologists have asserted that the drugs commonly considered for inclusion into such a polypill are older and therefore free of patent protection. We tested this assertion. This project was requested by the World Heart Federation (WHF).Methods, data and materialsTwo cardiologists from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
(26 reference statements)
0
6
0
Order By: Relevance
“…A lower-cost option is a polypill made from the combination of active substances that produce drug synergism. Its use and formulation with patent-free substances have been proposed as strategies to improve adherence and cost-effectiveness of treatment for CVD [110,111,112,113,114,115,116,117,118]. However, consistent evidence is needed to support generalized use.…”
Section: Discussionmentioning
confidence: 99%
“…A lower-cost option is a polypill made from the combination of active substances that produce drug synergism. Its use and formulation with patent-free substances have been proposed as strategies to improve adherence and cost-effectiveness of treatment for CVD [110,111,112,113,114,115,116,117,118]. However, consistent evidence is needed to support generalized use.…”
Section: Discussionmentioning
confidence: 99%
“…A lower-cost option is a polypill made from the combination of active substances that produce drug synergism. Its use and formulation with patent-free substances have been proposed as strategies to improve adherence and costeffectiveness of treatment for CVD [109][110][111][112][113][114][115][116][117]. However, consistent evidence is needed to support a generalized use.…”
Section: Cvdmentioning
confidence: 99%
“…Another barrier to the free implementation of the polypill are the patents for its components. A study in Canada and the United States assessed the availability of cardiovascular medication with free patents and found that only 40% of cardiovascular medications were totally patent free, 41 which could be a significant barrier for the worldwide marketing and distribution of the polypill. A potential solution to this issue is that the pharmaceutical companies who own the original patents bring the polypill to the market at an affordable price, or generic companies and government research agencies incentivize successful pricing models allowing its easy obtainment and implementation for adequate treatment.…”
Section: Limitations Of the Polypill Strategymentioning
confidence: 99%